Did the Bundesbank React to Stock Price Movements? - Pierre L. Siklos; Martin T. Bohl; Thomas Werner (Deutsche Bundesbank, 2003)
In this paper, we investigate the relationship between stock returns and short-term interest rates. Identification of the stock return-interest rate relation is solved by using a new technique that relies on the heteroskedasticity of shocks to stock market returns. We suggest some improvements to the identification technique and its justification, as well as providing some new findings. In particular, we ask whether the Bundesbank, prior to the European Central Bank taking responsibility for monetary policy in 1999, reacted systematically to stock price movements. In contrast to the results for the US, our empirical findings for the 1985 - 1998 period show a positive, but statistically insignificant, parameter for the relationship between German stock returns and short-term interest rates at the daily frequency. The same result is found at the monthly frequency. Nevertheless, the confidence bands are wide enough that we cannot entirely exclude the possibility of a reaction at lower frequencies. The results are extremely robust to alternative methods used to identify changes in heteroskedasticity. The evidence is, therefore, inconsistent with the hypothesis of a systematic reaction of the Bundesbank to every wiggle in German stock prices. Both the historical and institutional evidence are supportive of this conclusion. – – In diesem Diskussionspapier untersuchen wir den Zusammenhang zwischen Aktienkursveränderungen und Veränderungen der kurzfristigen Zinssätze. Die ökonometrische Identifikation dieses Zusammenhangs erfolgt mit Hilfe eines neuen Verfahrens, das die Heteroskedastie von Aktienkursveränderungen ausnutzt. Wir schlagen einige Verbesserungen und Rechtfertigungen zu diesem Verfahren vor und liefern neue empirische Befunde. Im Vordergrund der Betrachtungen steht die Frage, ob die Bundesbank vor der Übernahme der geldpolitischen Entscheidungen durch die Europäische Zentralbank im Jahre 1999 systematisch auf Veränderungen der Aktienkurse reagiert hat. Im Unterschied zu den verfügbaren Ergebnissen für die Vereinigten Staaten von Amerika, finden wir auf Basis von Tagesdaten zwar einen positiven, aber statistisch nicht signifikanten Parameter für die Reaktion des kurzfristigen Zinssatzes auf Änderungen des Aktienkurses. Auf der Grundlage von Monatsdaten ist der Parameter ebenfalls positiv und statistisch insignifikant. Die Konfidenzintervalle sind aber sehr breit, so dass eine Reaktion auf der niedrigeren Frequenz nicht völlig ausgeschlossen werden kann. Die empirischen Resultate sind sehr robust gegenüber unterschiedlichen Modellspezifikationen. Die empirische Evidenz widerspricht somit der These einer systematischen Reaktion der Bundesbank auf jede Bewegung am Aktienmarkt, was durch die historischen und institutionellen Gegebenheiten gestützt wird.
Keywords: 330; Geldpolitik; Zins; Zinspolitik; Heteroskedastizität; Schätzung; Deutschland